Ethnic units in the late Roman Army? The case of the equites dalmatae - Dziurdzik, Tomasz (Studia Europaea Gnesnensia, 2017)
The article relies on the case study of the equites Dalmatae to analyse the relationships between Late Roman military unit naming conventions and the recruitment patterns of the era. Of special importance is the question of the extent to which the army employed ethnic units, recruited from a particular population and using their own, traditional fighting styles. The conclusions are reached through a combination of historical and onomastic study, with special regard to the possible meanings of the term Dalmatae and the entities and identities it could have represented.